Quantitative Evaluation of Anion Exchanger Thermax A-127 A Pedagogical Approach - Ajay P. Ganorkar, (International Journal of Scientific Research in Science and Technology, 2024)
Ion exchange resins can be put to large variety of applications such as ion exchange chromatography, separation of substances and in analytical chemistry (1). The scope of these applications can be widely extended if information of the ion exchange equilibrium is available. In ion exchange reactions, precise determination of equilibrium constant in uni-bivalent ion exchange has been found to be very difficult due to lack of data on activity coefficients of the ions in the ion exchange resin. Helfferich (2) described the unavailability of these important data as a ‘missing link’ in the ion exchange equilibrium. No doubt various workers (3-6) attempted the determination of such equilibrium constants but they all ignored the activity coefficients. While in electrolytic solutions it has been possible to evaluate the mean activity coefficients of ions, this was not possible for ion exchange resins. Under such difficulties the best that can be done is to evaluate the equilibrium constant from experimental data on some logical basis. In the present study we have evaluated the equilibrium constant for the uni-bivalent ion exchange and mean activity coefficient of the ions in the resin, (R), on the basis of a certain chosen standard state for several ion exchange reactions.
Keywords: Ion Exchange Resins; Ion Exchange Reactions; Exchange Equilibrium